Does Experience Matter?: Analyzing the Impact of Experience in Cyberspace on the Opposition to Nuclear Energy - 김동근; 김서용 (인문사회 21, 2018)
This study aims to analyze the impact of experience factors on opposition action toward nuclear power in the online space. Due to the development of information and communication technologies, cyberspace has become a new field for forming social discourse. The importance of such cyberspace also applies to nuclear energy. However, there are few studies that analyze the effects of experience on opposition to nuclear energy in the internet space. This study conducted correlation and regression-based analyses by using a collected survey data. The results show that among risk perception paradigm factors, perceived risk, perceived benefit, trust, knowledge, and negative emotion have impact on the opposition to nuclear power. Among experience, the self-expression and interaction increase the opposition action. The information variables have no significant effect on the opposition. This study suggests that experience factor has a critical impact on the opposition to nuclear energy
Keywords: 원자력 에너지; 심리지각 패러다임; 원자력 반대; 경험; Nuclear Power Energy; Risk Perception Paradigm; Opposition to Nuclear Power; Experience; Social Interaction